Führungs- und Störgrößenaufschaltungen für lineare verteilt-parametrische Systeme - Deutscher, Joachim; Harkort, Christian (at - Automatisierungstechnik, 2010)
In this article the design of reference and disturbance feedforward controllers is considered for linear distributed-parameter systems, which are Riesz-spectral systems. Explicit expressions are derived for the feedforward controller. The design uses a two-degree-offreedom structure which enables an independent computation of the feedforward controller and of a state feedback controller that assigns the closed loop dynamics. A heat conductor is used to demonstrate the results of the contribution in simulations. © Oldenbourg Wissenschaftsverla
Keywords: Disturbance feedforward control; Linear distributed-parameter systems; Parametric approach; Reference feedforward control; Two-degrees-of-freedom control